2005
DOI: 10.1002/glia.20264
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of oncostatin M on astroglioma cells: Influence on cell proliferation, invasion, and expression of matrix metalloproteinases

Abstract: Oncostatin M (OSM), a cytokine of the interleukin-6 (IL-6) family, can either promote or inhibit cell growth in various normal and tumor cells. We addressed the effects of exogenous OSM on the proliferation and invasion of human astroglioma cells. In addition, we investigated one of the possible mechanisms involved: modulation of matrix metalloproteinase (MMP) expression and enzymatic activity. We found that OSM inhibited the proliferation of two human astroglioma cell lines (CH235-MG and U87-MG), and that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…In some glioblastoma cell lines, autocrine IL-6 expression resulted in constitutive activation of STAT-3, and neutralizing antibodies to IL-6 reduced STAT-3 activation, inhibited cell proliferation, and induced apoptosis (48). In a number of other human brain tumor cell lines, stimulation with IL-6, leukemia inhibitory factor, ciliary neurotrophic factor, or OSM resulted in induced STAT-3 activation (46), and treatment of human astroglioma cells with OSM increased the STAT-3 -dependent expression and activation of matrix metalloproteinase-9 and VEGF (59,60).…”
Section: Stat-3 Activation By Il-6 Cytokinesmentioning
confidence: 99%
“…In some glioblastoma cell lines, autocrine IL-6 expression resulted in constitutive activation of STAT-3, and neutralizing antibodies to IL-6 reduced STAT-3 activation, inhibited cell proliferation, and induced apoptosis (48). In a number of other human brain tumor cell lines, stimulation with IL-6, leukemia inhibitory factor, ciliary neurotrophic factor, or OSM resulted in induced STAT-3 activation (46), and treatment of human astroglioma cells with OSM increased the STAT-3 -dependent expression and activation of matrix metalloproteinase-9 and VEGF (59,60).…”
Section: Stat-3 Activation By Il-6 Cytokinesmentioning
confidence: 99%
“…In the last fifty years, multimodality therapy has achieved only modest gains for malignant gliomas (1), which is one of the most common and fatal primary tumors in adults (2) and the second cause of cancer-related death in the young adults (3). It is generally believed that invasion and angiogenesis both play critical roles in the formation of recurrent tumors (4).…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis showed that the tumor cells have functional OSM receptors and signal transduction systems, but the effects of OSM expression on proliferation, apoptosis and migration in brain tumors remain unclear (7,14,20,21). In this study we used a genome wide microarray analysis to investigate the expression patterns of OSM responsive genes in U1242MG.…”
Section: Discussionmentioning
confidence: 99%
“…OSM is a member of the interleukin (IL)-6 cytokine family which includes IL-6, IL-11, leukemia inhibitory factor (LIF), ciliary neurotrophic factor (CNTF), cardiotrophin-1 (CT-1) and cardiotrophin-like cytokine (CLC) (7,8). These cytokines are involved in the regulation of the acute-phase to injury, infection, haematopoiesis, liver and neuronal regulation, embryonal development and fertility (9).…”
Section: Introductionmentioning
confidence: 99%